Community structure of the Fiddler Crab (Uca spp.) at Bahak Indah Beach, Tongas, Probolinggo – East Java - Nur Malichatin; Husain Latuconsina; Hasan Zayadi (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
The fiddler crab (Uca spp.) is a type of animal belonging to the crustacean group that lives on the coast of Bahak Indah, Tongas, Probolinggo. The high level of anthropogenic activity on the beach of Bahak Indah makes the fiddler crab community increasingly depressed and its habitat decreasing. The purpose of this study was to compare the community structure of fiddler crabs at Bahak Beach, Tongas, Probolinggo. The study was conducted in January – February 2022. The determination of observation stations was purposive based on the consideration of the presence and absence of mangrove vegetation. Sampling of fiddler crabs used a systematic sampling method using transects and plots. Community structure data analysis includes diversity, uniformity, and dominance indices displayed in graphical form. Based on the results of the study found 4 types of fiddler crabs in Bahak Indah Beach, namely Uca cryptica, Uca perplexa, Uca coarctata, and Uca dussumieri. The value of diversity on the beach with mangrove habitat is in the medium category, while on the beach habitat without mangrove vegetation it is in the low category. The uniformity value obtained in mangrove habitats is in the high category, while in coastal habitats without mangrove vegetation it is found in the medium category. On the other hand, the dominance index value is in the low category in coastal habitats with mangrove vegetation, and the moderate category in coastal habitats without mangrove vegetation. The relationship between the Diversity (H') of the fiddler crab and the environmental conditions of the Bahak Indah Beach waters is that it has a positive correlation with water pH parameters with sufficient correlation and soil pH with a strong correlation. While the correlation with temperature parameters is strong but negative. Likewise, salinity is quite strong but negative.